2006
DOI: 10.1055/s-2006-944835
|View full text |Cite
|
Sign up to set email alerts
|

PillCam colon capsule endoscopy compared with colonoscopy for colorectal tumor diagnosis: a prospective pilot study

Abstract: CCE showed promising accuracy compared with colonoscopy. This new noninvasive technique deserves further evaluation as a potential CRC screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
2
24

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(173 citation statements)
references
References 12 publications
5
142
2
24
Order By: Relevance
“…[1] и N. Schoofs и соавт. [7] получили аналогичные результаты, согласно которым количество пациентов с адекватной под-готовкой составило 84% и 88%, а с неадекватной -16% и 12% соответственно.…”
Section: результаты исследованияunclassified
“…[1] и N. Schoofs и соавт. [7] получили аналогичные результаты, согласно которым количество пациентов с адекватной под-готовкой составило 84% и 88%, а с неадекватной -16% и 12% соответственно.…”
Section: результаты исследованияunclassified
“…The Pillcam COLON capsule endoscopy (Given Imaging Ltd, Yoqneam, Israel) has also shown promising results as a new modality to evaluate for colorectal cancer screening [94][95][96][97][98][99][100][101]. It is in clinical trials in Europe.…”
Section: New Capsulesmentioning
confidence: 99%
“…Three studies were performed with this first colon capsule [Van Gossum et al 2009;Eliakim et al 2006;Schoofs et al 2006] which demonstrated three important features: the capsule could transit through the entire colon while taking images; the bowel was adequately clean in 80% of cases; and, finally, the capsule was able to identify pathological findings such as polyps, tumors, inflammation and diverticular disease. The disappointment with this colon capsule was the lower sensitivity in identifying patients with colonic polyps as compared with standard colonoscopy [Van Gossum et al 2009].…”
Section: Visualization Of the Mucosa And Bowel Cleansingmentioning
confidence: 99%